Aberrant Antigen Expression in Children with Acute Leukemia A Flow Cytometric Analysis (Bangladesh Journal of Medical Microbiology, 2018)
The primary clinical tool for predicting the lineage potential of leukemic blasts is the characterization of protein expression by immunophenotyping. It is common for acute leukemias to aberrantly express protein markers more typically associated with other lineages. Therefore, this study was designed to assess the frequency of aberrant antigens expression in childhood acute leukemia. Peripheral blood and bone marrow samples were collected from 76 clinically suspected and morphologically diagnosed untreated cases of acute leukemia (children of 0-